Кавказька складова у фінальному палеоліті і мезоліті Південної України - Оленковський, М.П. (Археологія, 1996)
У статті поставлено питання про можливість кавказького впливу на формування культур заключного періоду пізнього палеоліту півдня України. Наведено дані про кавказьку підоснову північно-кавказької культури та про окремі її елементи в осокорівській культурі. Статья раскрывает один из компонентов сложной проблематики формирования и развития культур финального палеолита и мезолита юга Украины. Аргументируется кавказское происхождение северо-приазовской культуры как результата развития каменнобалковской культуры. Приводятся данные об участии северо-приазовской культуры в сложении финальнопалеолитической осокоровской. Автор поддерживает мнение ряда исследователей о возможности трансформации осокоровской культуры в мезолитическую гребениковскую культуру, однако считает, что между ними существовал еще значительный культурно-хронологический хиатус, который, вероятно, заполняет культурный тип памятников, представленный раннемезолитическим местонахождением Анастасивка. The article deals with one. of components of the complex problems of forming and developing the Final Paleolithic and the Mesolithic cultures in the southern area of Ukraine. The Caucasian origin of the Northern Asov Sea Coast culture, resulting from a development of the Kamennobalkovskaya one, is proved, Data is given on the participation of the Northern Azov Sea Coast Area culture in forming the Osokorovskaya one in the Final Paleolithic. The author supports the opinion of several investigators on the possibility of transforming the Osokorovskaya culture into the Grebenikovskaya one of the Mesolithic. Nevertheless, he believes a significant cultural-chronological hiatus still exists between these cultures, which, probably, might be filled by the cultural type of relics, presented by the location of Anasiasivka village in the Early Mesolithic Period.